Talent identification and development in judo: A systematic review - Aline Aparecida de Souza Ribeiro; Francisco Zacaron Werneck; João Guilherme Vieira; Leandro Sant’Ana; Kathryn Johnston; Joseph Baker; Jeferson Macedo Vianna (Current Issues in Sport Science, 2025)
This review synthesizes the existing literature about talent identification and development in judo and provides evidence-based suggestions to help researchers and practitioners in this area. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used to identify relevant studies (n = 45). The mean quality of the evidence was 94.0%. Most of the studies were published between the years 2014 and 2021 with cross-sectional designs and group comparisons or performance prediction. Studies used batteries of tests focused on expert or advanced samples and measured individual constraints. Few studies examined female samples, psychological skills or biological maturation. Only 20% of the studies used multivariate analyses. On closer examination, there was a high degree of variability in the indicators that were found to discriminate between skilled and less-skilled judo athletes, predict performance and/or predict career pathway. Research in talent identification and development in judo has generally focused on individual constraints related to anthropometric and physiological characteristics, and technical skills in cross-sectional designs. Very little is known about what talent indicators discriminate high skilled judo athletes or predict actual performance or future success. Future research should adopt multidimensional and longitudinal approaches that integrate existing findings about the maturational, psychological and environmental aspects of judo for tracking the most talented judo athletes, especially in female samples.